2017
DOI: 10.37134/ajelp.vol5.2.2017
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Awareness Strategies For Listening Comprehension

Abstract: Language educators tend to focus extensively on reading and writing skills. Listening activities are often carried out only to test the students' abilities which may lead to their anxiety and apprehension (Vandergrift, 1999). Generally, many students face difficulty in their listening assessments. Students need to apply certain mental steps or operations in listening to encounter their listening problems. These mental steps are referred to as strategies to assist the learners to achieve a reasonable listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…ese findings are in line with Chang [46], Khiewsod [39], and Chin et al [47]. Personal knowledge scores certify that listening (in English) is difficult for them, and this might be the reason they translated the oral texts e responses to the mental translation strategies were more than 57% in all students.…”
Section: Discussionsupporting
confidence: 87%
“…ese findings are in line with Chang [46], Khiewsod [39], and Chin et al [47]. Personal knowledge scores certify that listening (in English) is difficult for them, and this might be the reason they translated the oral texts e responses to the mental translation strategies were more than 57% in all students.…”
Section: Discussionsupporting
confidence: 87%
“…How strategy and tactics influence the listening achievement was reported (Chin et al, 2017;Goh & Hu, 2014;Tanewong, 2019). The research findings claimed that students' listening achievement was influenced by metacognitive instruction and the student's awareness of the strategies used.…”
Section: Discussionmentioning
confidence: 96%
“…The five factors in the MALQ (i.e., problem-solving, planning and evaluation, mental translation, personal knowledge, directed attention) are used in this study to elicit students' use of metacognitive strategies while listening to an oral text. Many empirical studies have shown that a skilled listener uses more metacognitive strategies while listening (Goh & Yusnita, 2006;Looi-Chin et al, 2017;Vandergrift, 2003;Vandergrift & Tafaghodtari, 2010).…”
Section: Metacognitive Listening Strategiesmentioning
confidence: 99%
“…A more recent study was conducted by Looi-Chin et al (2017) where they attempted to identify the level of metacognitive strategies used by college students (N = 100) in Malaysia while listening, and the effect of these strategies on their listening test scores. The authors used the MALQ, which was designed by Vandergrift et al (2006), to elicit students' use of metacognitive strategies while listening in English.…”
Section: Directed Attentionmentioning
confidence: 99%